A novel multi-layered immune structural model for peripheral blood immune scoring in cancer patients: perspective and hypothesis - Jin, Hao (Frontiers in Immunology, 2025)
Accurately assessing and quantifying immune competence in cancer patients remains a major challenge in tumor immunology. Traditional intratumoral immune profiling, such as tissue pathology and tissue-based cytometry techniques, faces significant challenges due to difficulties in tissue sampling, spatial heterogeneity, and technical limitations. In contrast, peripheral blood immune profiling is a more practical and reproducible approach, providing valuable insights into systemic immune status. This article introduces a novel immune structural model, inspired by protein structural hierarchy, to classify immune components into three hierarchical levels: primary, secondary, and tertiary immune structures. We hypothesize that this model can provide a systematic framework for constructing an immune scoring system (ISS) that integrates multi-dimensional immune information from flow cytometry, cytokine profiling, and immune checkpoint molecule assessments. The proposed model offers a new way to assess immune status and could serve as a valuable tool for clinical personalized treatment and prognostic evaluation.